Biosynthesis of Alkylcitric Acids in Aspergillus niger Involves Both Co-localized and Unlinked Genes - Palys, Sylvester; Pham, Thi Thanh My; Tsang, Adrian (Frontiers in Microbiology, 2020)
Filamentous fungi are an abundant source of bioactive secondary metabolites (SMs). In many cases, the biosynthetic processes of SMs are not well understood. This work focuses on a group of SMs, the alkylcitric acids, each of which contains a saturated alkyl “tail” and a citrate-derived “head”. We initially identified their biosynthetic gene cluster and the transcriptional regulator (akcR) involved in the biosynthesis of alkylcitrates in the filamentous fungus Aspergillus niger by examining the functional annotation of SM gene clusters predicted from genomic data. We overexpressed the transcription regulator gene akcR and obtained from a litre of culture filtrate 8.5 grams of extract containing seven alkylcitric acids as determined by NMR. Hexylaconitic acid A comprised ~ 95% of the total production, and four of the seven identified alkylcitrates have not been reported previously. Analysis of orthologous alkylcitrate gene clusters in the Aspergilli revealed an in-cluster cis-aconitate decarboxylase gene (cadA) in A. oryzae and A. flavus, which in A. niger is located on a different chromosome. Overexpression of the A. niger cadA and akcR genes together shifted the profile of alkylcitrates production from primarily hexylaconitic acids to mainly hexylitaconic acids. We also detected two additional, previously unreported, alkylcitric acids in the double overexpression strain. This study shows that phylogenomic analysis together with experimental manipulations can be used to reconstruct a more complete biosynthetic pathway in generating a broader spectrum of alkylcitric compounds. The approach adopted here has the potential of elucidating the complexity of other SM biosynthetic pathways in fungi.